ANALYSIS OF GAAS SCHOTTKY CONTACT TRAVELING-WAVE OPTICAL COUPLERS - CHOI, WJ; LEE, JI; KANG, KN; HONG, SC; CHO, KM (KOREAN PHYSICAL SOC, 1993)
Traveling wave directional coupler-type electro-optic modulators based on GaAs Schottky contact microstrip lines are modeled and analyzed. The microwave propagation including losses in the structure is described by a simple quasi-TEM model. The lightwave propagation is calculated numerically including multiple layer effects as well as Schottky metal cladding effects. A simple figure of merit is used to compare and optimize structures. The results show that the effects of microwave attenuation dominate those of velocity and impedance mismatching at more than 1 GHz and that the device performance is strongly dependent on the operating voltage.
Keywords: ELECTROOPTIC MODULATORS; TRANSMISSION-LINE